Luteal blood flow and luteal function - Takasaki Akihisa; Tamura Hiroshi; Taniguchi Ken; Asada Hiromi; Taketani Toshiaki; Matsuoka Aki; Yamagata Yoshiaki; Shimamura Katsunori; Morioka Hitoshi; Sugino Norihiro (BMC, 2009)
Abstract Background Blood flow in the corpus luteum (CL) is associated with luteal function. The present study was undertaken to investigate whether luteal function can be improved by increasing CL blood flow in women with luteal phase defect (LFD). Methods Blood flow impedance in the CL was measured by transvaginal color-pulsed-Doppler-ultrasonography and was expressed as a resistance index (RI). The patients with both LFD [serum progesterone (P) concentrations < 10 ng/ml during mid-luteal phase] and high CL-RI (≥ 0.51) were given vitamin-E (600 mg/day, n = 18), L-arginine (6 g/day, n = 14) as a potential nitric oxide donor, melatonin (3 mg/day, n = 13) as an antioxidant, or HCG (2,000 IU/day, n = 10) during the subsequent menstrual cycle. Results In the control group (n = 11), who received no medication to increase CL blood flow, only one patient (9%) improved in CL-RI and 2 patients (18%) improved in serum P. Vitamin-E improved CL-RI in 15 patients (83%) and improved serum P in 12 patients (67%). L-arginine improved CL-RI in all the patients (100%) and improved serum P in 10 patients (71%). HCG improved CL-RI in all the patients (100%) and improved serum P in 9 patients (90%). Melatonin had no significant effect. Conclusion Vitamin-E or L-arginine treatment improved luteal function by decreasing CL blood flow impedance. CL blood flow is a critical factor for luteal function.